Mpox Outbreak in Previously Non-Endemic Countries: A Review on Impact on Asia - Madushani Wickramasinghe; Manjula Weerasekera; Nilanka Perera (SAGE Publishing, 2024)
Mpox (human mpox) is an opportunistic viral zoonosis that bears a strong resemblance to smallpox. The virus is divided into 2 distinct clades, clade I and clade II, which were originally confined to the moist forest regions of Africa. However, due to air travel and the exotic pet trade, these clades have spread globally. As immunity from smallpox vaccination declined, Mpox emerged as the most significant viral infection affecting humans within the Orthopoxvirus genus. While sporadic cases occurred worldwide, the largest Mpox outbreak outside Africa took place in 2022, prompting the WHO to declare a global public health emergency. Asia plays a pivotal role in both hosting and contributing to the spread of Mpox, driven by socio-economic factors such as high population density, widespread illegal wildlife trade, and a continuous rise in air travel. The increasing number of Mpox cases in Asia poses a significant challenge to healthcare systems, especially during times of global economic crisis. Strengthening diagnostic capabilities and infrastructure, while sustainably utilizing available resources to target high-risk populations, will be essential in addressing the Mpox threat in the region.